Tinjauan Viktimologi dan Penerapan Hukum Pidana Tentang Tindak Pidana dalam Undang-Undang ITE (Studi Kasus Putusan PN Tanjung Balai Karimun No. 96/PID.SUS/2021/PN.TBK) - Alaidid, Muannas; Said, Yusuf Muhammad (FOCUS, 2025)
This research aims to examine the application of Article 27 paragraph (3) of the Electronic Information and Transaction Law (ITE Law), especially in the context of online news. There are still many law enforcement officials, such as the Police and the Attorney General's Office, who do not understand that not all information cases can be categorised as violations of the article. For example, individuals who upload news from websites registered with the Press Council are still prosecuted for alleged violations of the ITE Law. In the digital era, the law must adapt quickly to accommodate technological innovation, cybercrime and digital privacy. This study uses a normative juridical method with systematic analysis of legal materials, including the Decision of the Tanjung Balai Karimun District Court No. 21/Pid.Sus/2021/TBK. The results show that the concepts of victimology and press law are often ignored in the application of this article. Constitutional Court Decision No. 78/PUU-XXI/2023 states that defamation in the Criminal Code and Article 27 paragraph (3) of the ITE Law is conditionally unconstitutional. Therefore, further socialisation is needed to prevent legal misunderstandings in the implementation of the article.